Brachial-ankle pulse wave velocity for predicting functional outcomes in patients with cryptogenic stroke. (November 2019) - Han, Minho; Kim, Young Dae; Park, Hyung Jong; Hwang, In Gun; Choi, Junghye; Ha, Jimin; Heo, Ji Hoe; Nam, Hyo Suk
Highlights: The prognosis of CS patients is largely undetermined. baPWV is a simple, non-invasive indicator of arterial stiffness. No study has investigated the association of the baPWV with the prognosis of CS. We investigated whether baPWV could predict the poor outcome of CS patients. baPWV was independently associated with poor functional outcomes in CS patients. Abstract: Even after extensive standard evaluation, the probable cause of stroke in some patients remains unclear; this condition is defined as cryptogenic stroke (CS). The prognosis of patients with CS is largely undetermined. We investigated whether higher brachial-ankle pulse wave velocities (baPWVs) can predict poor functional outcomes at 3 months after stroke onset in these patients. We investigated patients with CS with first-ever acute cerebral infarction who underwent baPWV measurements. The stroke subtypes were classified using the Trial of ORG 10172 in Acute Stroke Treatment classification. Poor functional outcomes were defined as modified Rankin Scale scores of >2 at 3 months after stroke onset. In total, 595 patients with CS were included; among them, 360 were men (60.5%). Their mean age was 65.0 ± 12.4 years. One-hundred-eleven patients (18.7%) had poor functional outcomes. In the multivariable logistic regression analysis, the cutoff baPWV value based on the receiver-operating characteristic curve was >1968 cm/s, which was determined as a strong independent predictor (OR 3.159, 95% CI 1.487–6.715, p  = 0.003). The OR of the cutoff value was higher in the patients with CS with initial National Institutes of Health Stroke Scale (NIHSS) scores of ≥5 (OR 4.252, 95% CI 1.596–11.324, p  = 0.004); that in the patients with initial NIHSS scores of <5 was not significant (OR 1.671, 95% CI 0.620–4.505, p  = 0.310). baPWV measurement during the acute stroke phase might be useful in identifying patients with CS at high risks of having a poor neurological prognosis.